Pengaruh Metode Part and Whole terhadap Hasil Belajar Headstand Senam Lantai Pada Siswa SMP Negeri 1 Pomalaa - Juhanis Juhanis; Hasmyati Hasmyati (Seminar Nasional LP2M UNM, 2019)
This research is a type of quantitative research through a one group pretest-posttest design experimental approach that aims to find out; The effect of part and whole methods on the learning outcomes of the floor gymnastic headstand on the students of Pomalaa 1 Middle School. The population is all students of Pomalaa 1 Middle School. The sample used was grade III students as many as 30 people. The sampling technique is Proportionv Sampling. Data collection techniques in this study used the test. The instrument used in this study was a performance test of the floor gymnastic headstand motion. Data analysis techniques used the t test analysis and had previously been tested for normality and homogeneity through the SPSS 21 program at a significant level α = 0.05. Based on the analysis of the results of the research and discussion, it can be concluded that: there is a significant influence of the part and whole method on the learning outcomes of the floor gymnastic headstand students of Pomalaa 1 Middle School with a tcount of -15,397 with a significance value of 0,000 <0.005. The mean value of the headstand learning outcomes of the initial floor exercise or pre-test was 64.13 while the post-test rose to 79.77.